Usability and User Experience Analysis of the HumicPrint Mobile Application Using the USE Questionnaire and UEQ - Febry Andrias; Wahyu Teja Kusuma; Ahsanun Naseh Khudori (Universitas Islam Indragiri, 2026)
This study aims to evaluate the usability and user experience of the HumicPrint mobile application as a digital certificate management system. A descriptive quantitative approach was employed, involving 26 respondents. Usability was evaluated using the USE Questionnaire, which measures four dimensions: usefulness, ease of use, ease of learning, and satisfaction. User experience was assessed using the User Experience Questionnaire (UEQ), with the results analyzed using the UEQ Data Analysis Tool and compared against the established UEQ benchmark. The usability evaluation yielded an overall mean score of 86.23%, indicating an excellent level of usability. The scores for the individual dimensions were 86.26% for usefulness, 86.12% for ease of use, 86.30% for ease of learning, and 86.12% for satisfaction. The user experience evaluation showed that the Attractiveness and Efficiency dimensions were rated Above Average, while Stimulation achieved a Good rating. However, the Perspicuity, Dependability, and Novelty dimensions remained in the Below Average category. Overall, the findings indicate that the HumicPrint mobile application provides an excellent level of usability and a positive user experience. Nevertheless, improvements to the Perspicuity, Dependability, and Novelty dimensions are recommended to further enhance the overall quality of the user experience.